Thermal analysis model of a building equipped with green roof and its energy optimization - Rahim Zahedi; Sareh Daneshgar; Omid Noudeh Farahani; Alireza Aslani (Nature-Based Solutions, 2023)
In this research, the simulation and modeling of the energy use for a two-story theoretical building which is equipped with the green roof in three various climates of Iran (Tabriz: cold and dry; Tehran: mild and dry; and Bandar Abbas: tropical and dry) has been done. The purpose of this simulation is to show the impacts of the green roof on reducing thermal loads of a building and also its role in reducing the heat flux passing through the roof of the building. The procedure is that first this building takes its model in one software and then this 3D model is delivered to the Energy Plus simulation engine, then simulation is done in different period of times. For each city, a normal building with an asphalt roof was simulated along with a completely similar building which has the vegetation cover rather than asphalt in the last layer of its roof and the output results are compared with each other. The simulation results show that by applying the green roof, the basic state of annual electricity consumption in the cities of Tehran, Tabriz and Bandar Abbas decrease 16.3%, 12.5% and 23%, respectively. According to the values obtained, using the green roof is more efficient in tropical areas (Bandar Abbas) than cold areas (Tabriz). Bandar Abbas with tropical and dry climate needs much energy to cool the environment in the summer, but due to the balanced temperature in the cold months and no need of energy for heating, the amount of energy consumption in Bandar Abbas is much lower than other cities during the year. Also, the sensitization analysis tests have shown that the energy consumption of building is strongly dependent on the thickness of the soil parameters changes and plant density of the green roof structure, therefore more thickness of the applied soil has better thermal insulation. The economic savings per year based on the use of a green roof for the building, located in Tehran, Tabriz and Bandar Abbas are 562, 660 and 381 $ respectively.